Ultrasound Triggers Hypericin Activation Leading to Multifaceted Anticancer Activity - Federica Foglietta; Roberto Canaparo; Simone Cossari; Patrizia Panzanelli; Franco Dosio; Loredana Serpe (MDPI AG, 2022)
The use of ultrasound (US) in combination with a responsive chemical agent (sonosensitizer) can selectively trigger the agent's anticancer activity in a process called sonodynamic therapy (SDT). SDT shares some properties with photodynamic therapy (PDT), which has been clinically approved, but sets itself apart because of its use of US rather than light to achieve better tissue penetration. SDT provides anticancer effects mainly via the sonosensitizer-mediated generation of reactive oxygen species (ROS), although the precise nature of the underpinning mechanism is still under debate. This work investigates the SDT anticancer activity of hypericin (Hyp) in vitro in two- (2D) and three-dimensional (3D) HT-29 colon cancer models, and uses PDT as a yardstick due to its well-known Hyp phototoxicity. The cancer cell uptake and cellular localization of Hyp were investigated first to determine the proper noncytotoxic concentration and incubation time of Hyp for SDT. Furthermore, ROS production, cell proliferation, and cell death were evaluated after Hyp was exposed to US. Since cancer relapse and transporter-mediated multidrug resistance (MDR) are important causes of cancer treatment failure, the US-mediated ability of Hyp to elicit immunogenic cell death (ICD) and overcome MDR was also investigated. SDT showed strong ROS-mediated anticancer activity 48 h after treatment in both the HT-29 models. Specific damage-associated molecular patterns that are consistent with ICD, such as calreticulin (CRT) exposure and high-mobility group box 1 protein (HMGB1) release, were observed after SDT with Hyp. Moreover, the expression of the ABC transporter, P-glycoprotein (P-gp), in HT-29/MDR cells was not able to hinder cancer cell responsiveness to SDT with Hyp. This work reveals, for the first time, the US responsiveness of Hyp with significant anticancer activity being displayed, making it a full-fledged sonosensitizer for the SDT of cancer.